La Habana, 1930: Lorca entre raza y cultura - Birkenmaier, Anke (Revista de Antropología Social, 2008)
This essay analyzes Federico Garcia Lorca’s interest in Afro-Cuban culture. It takes into account his impact in Cuba during and after his visit in 1930, and his poetry and correspondence written at that time to, in this fashion -in this way-, construct the “anthropological space” -Augé- of Havana’s culture in that period. The author then compares Lorca’s contribution to the anthropology of Fernando Ortiz and his changing approach to race and culture.